To reflect across the x-axis, multiply y by -1.

\(\displaystyle{A}{\left({1},{2}\right)}\to{A}'{\left({1},-{2}\right)}\)

\(\displaystyle{B}{\left({3},{4}\right)}\to{B}'{\left({3},-{4}\right)}\)

\(\displaystyle{C}{\left({4},-{1}\right)}\to{C}'{\left({4},{1}\right)}\)

The needed coordinates are \(\displaystyle{A}'{\left({1},-{2}\right)},{B}'{\left({3},-{4}\right)}{\quad\text{and}\quad}{C}'{\left({4},{1}\right)}\).

\(\displaystyle{A}{\left({1},{2}\right)}\to{A}'{\left({1},-{2}\right)}\)

\(\displaystyle{B}{\left({3},{4}\right)}\to{B}'{\left({3},-{4}\right)}\)

\(\displaystyle{C}{\left({4},-{1}\right)}\to{C}'{\left({4},{1}\right)}\)

The needed coordinates are \(\displaystyle{A}'{\left({1},-{2}\right)},{B}'{\left({3},-{4}\right)}{\quad\text{and}\quad}{C}'{\left({4},{1}\right)}\).